Exploration of Food Knowledge Transmission of Ethnic Dishes of Muslim-Migrated Ethnic Groups - Rebeca Mulok; Ryan Chandler Biscante; Hazel Maree Juanillas (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
Ethnic dishes play a crucial role in defining and preserving cultural identity. Upon the migration of Muslim ethnic groups to urbanized areas, their everyday life, cultural practices, and food intake behavior may be heavily influenced by the new environment. This led the researchers to investigate the transmission of food knowledge about ethnic dishes among Muslim-migrated ethnic groups. Most studies on the transmission of food knowledge have focused on Malay, Ainu, and other indigenous groups in other countries. This research addresses the lack of empirical studies on the food knowledge transmission of Muslim-migrated ethnic groups. Moreover, migration to a non-Muslim region changes the setting of passing on ethnic food knowledge from one generation to the next. This qualitative research employed the philosophical paradigm of interpretivism to investigate the transmission of ethnic food knowledge among Muslim migrant families. Using a semi-structured interview, the participants consisted of four sets of parent-child pairs selected through purposive sampling. Participants described the type of knowledge transmitted, strategies for transmitting ethnic food knowledge from parents to children, and adjustments made to ingredients due to limited access to raw materials. Findings explain further the translocalism framework, which initially focused only on migration networks, remittances, geography, and social resilience. This research demonstrates how Muslim migrants sustain their ethnic food knowledge traditions and transmission, further adding cultural remittance to the framework, despite moving to other regions in the Philippines.